The gravity of tobacco smuggling. Predicting bilateral illicit cigarette flows from aggregate data - Damijan, Jože (Teorija in praksa, 2022)
International tobacco smuggling remains an important concern for governments, tobacco manufacturers and health experts alike. While often linked to other forms of illegal activities, it also directly impacts government tax and health policies. Knowledge of factors that contribute to illicit tobacco trade and the existence of smuggling routes is strongly hampered by the lack of reliable data on bilateral flows of illicit tobacco. Therefore, reconstructing the trafficking routes and estimating the size of cross-border illicit flows are crucial steps for gaining better understanding of these crimes and enforcing actions aimed at countering them. This study is the first to use grav-ity estimation techniques to decompose aggregate illicit cigarette inflows for which data are available into their bilateral components. Our approach is a simple and effective method that can serve as a complement to other methods of pinpointing international trafficking flows such as empty discarded pack data or network analysis to help in the fight against illicit tobacco flows. Policymakers, customs officials as well as law enforcement can employ the presented methods as an additional tool in the fight against illicit trade.
Keywords: Cigarete; kazniva dejanja; Tihotapstvo; tobak; trgovske poti; zdravstvena politika